Defining isotopic signatures of potential procurement sources: A case study in the Mesa Verde region of the US Southwest. (February 2022) - Burlot, Jacques; Schollmeyer, Karen; Renson, Virginie; Brenner Coltrain, Joan; Werlein, Amanda; Ferguson, Jeffrey R.
Highlights: New Sr and O isotope analyses allow to estimate regional signatures in the Mesa Verde Region (Southwest US) The McElmo Dome area is represented by a uniquely narrow range of Sr values. A correlation of plant δ 18 O with elevation is observed within Mesa Verde Region. The study expands the existing database of isotopic signatures for the US Southwest. Abstract: Combining strontium and oxygen isotope analyses has proved useful in determining animal procurement sources in archaeological case studies. In this paper, we analysed 87 Sr/ 86 Sr and δ 18 O of 55 rodents from archaeological contexts and 94 plants of the Mesa Verde and McElmo Dome regions (US Southwest) to estimate their regional isotopic signatures. We asked to what extent the new isotopic data would allow us to isolate one region from another, thus providing a background for interpreting fauna acquisition strategies. The results clearly show trends in bioavailable Sr across the Mesa Verde landscape. The lower 87 Sr/ 86 Sr values are synonymous with areas composed of igneous rock, while the highest values correspond, for the most part, to the San Juan Mountains, a region that likely provided large game hunting opportunities. Moreover, the McElmo Dome area associated with the sites under study is represented by a uniquely narrow range of Sr values suggesting that prey acquired outside a 10 km foraging range from such sites will be identifiable. Although plant oxygen isotope data did not further differentiate specific zones within the studied area, the significant correlation of plant δ 18 O with elevation will be useful for archaeologists to examine large game hunting strategies. Furthermore, this study expands the existing database of isotopic signatures for the American Southwest and, in particular, the San Juan Basin and its surroundings.